(untitled) (Research, Society and Development, 2022)
Agribusiness has an important representation in the economy of Brazil and Rondônia, and in the state, beef cattle is the activity that stands out the most. In the development of their work activities, rural workers are exposed to various environmental risks (physical, chemical, biological, ergonomic and accidents) and knowing them was the objective. Through a bibliographic study, the objective was to verify the most common practices of rural work, identifying the occupational risks of these activities and a survey of statistical data from Social Security and INSS on the record of accidents and occupational diseases. In rural areas, there is a great diversification of activities and tasks performed with family labor, therefore, there is a great diversity of risks to which workers are exposed and, consequently, a diversity of accidents and occupational diseases. Preventive actions must be carried out constantly to reduce risks, highlighting the maintenance of tools, machinery, and equipment, the use of personal protective equipment, proper use of chemicals, and awareness of the risks in order to maintain the physical and mental integrity of the worker.